Analisis Model Kepemimpinan Situsional dalam Pengembangan Organisasi Mall Pelayanan Publik (Studi Kasus pada Wali Kota Payakumbuh) - Siallagan, Posmaria; Koeswara, Hendri; Isfarudi, Isfarudi (PUBLICNESS: Journal of Public Administration Studies, 2025)
This study aims to describe and analyze the performance of the Payakumbuh City Government by referring to the Leadership Style adopted by the Mayor of Payakumbuh in carrying out all activities during his tenure of 5 years. This answers that the success of a regional government cannot be separated from the important role of the region itself. The regional head is responsible for progress and development in the region, including Paykumbuh City, which has succeeded in implementing a Public Service MALL by getting first place in 2022 for the best service delivery at the West Sumatra Province level. This research uses a qualitative research method with data collection techniques through interviews, observation and documentation. Informants come from the mayor himself. The results of this study indicate that the situational leadership model used by the Mayor of Payakumbuh has been implemented well so that it has an impact on the success received by the Payakumbuh City government, with changing situations the Mayor of Paykumbuh is able to provide maximum service to his staff.